Evaluasi dan Perbaikan Pengalaman Pengguna Menggunakan User Experience Questionnaire (UEQ) dan Heuristic Evaluation (HE) Pada Aplikasi Mobile Info BMKG - Abid Bagus Kurniawan; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile app of Info BMKG is a government application that provides an early warning, earthquake, weather, climate, and etc according to its scope. Based on the observations, interviews, and several responses in the Playstore comment column, various problem were found on the application that could make the user experience worse. To reduce any issues related to user experience, therefore an evalation is required to improve its user interface. This research is conducted with the UEQ (User Experience Questionnaire) method to measure the quality of the user experience level and HE (Heuristic Evaluation) to specify a problem(s) for the evaluator. The first evaluation is found that the BMKG app has a neutral user experience level and â€badâ€ rank resulted from the UEQ benchmark in 4 scales which are Attractiveness, Perspicuity, Efficiency, and Novelty and acquired a â€below averageâ€ category in 2 scales which are Dependability and Stimulation. Besides that, as much as 17 issues have been discovered by the evaluator and a list of design fix recommendations have been provided. The design fixes are then re-measured where it is discovered that there is a significant rise in the user experience level that results in a positive level and the UEQ benchmark category for Attractiveness, Efficiency, Dependability, Stimulation and Novelty is raised to a â€goodâ€ category, while the Perspicuity scale is measured in the â€aboveâ€ category.